2019
DOI: 10.1016/j.ibror.2019.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Combination antiretroviral therapy (cART)-induced hippocampal disorders: Highlights on therapeutic potential of Naringenin and Quercetin

Abstract: HighlightsNaringenin and Quercetin decrease ROS and potentiate enzymatic antioxidant production in the hippocampus.cART induced marked cytoplasmic shrinkage and several pyknotic nuclei in the dentate gyrus and cornus ammonis region.Naringenin and Quercetin attenuates cART-induced upregulation of monoamine oxidase-B expression in neurons.Naringenin and Quercetin also ameliorates cART-induced spatial memory impairments.Naringenin and Quercetin acted as effective antioxidants in vivo against cART-induced neurotox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 58 publications
2
9
1
Order By: Relevance
“…The oxidative stress markers in hippocampus were measured: superoxide dismutase (SOD), malonic dialdehyde (MDA), and glutathione (GSH) (Jiang et al, 2017;Al-Amin et al, 2018). The protein levels of interleukin (IL)-1β, IL-6 and TNF-α were evaluated by specific ELISA kits following manufacturer's instructions (Akang et al, 2019). The commercial kits for examining these parameters were purchased from Nanjing Jiancheng Bioengineering Institute (Nanjing, China).…”
Section: Enzyme-linked Immunoabsorbent Assaymentioning
confidence: 99%
“…The oxidative stress markers in hippocampus were measured: superoxide dismutase (SOD), malonic dialdehyde (MDA), and glutathione (GSH) (Jiang et al, 2017;Al-Amin et al, 2018). The protein levels of interleukin (IL)-1β, IL-6 and TNF-α were evaluated by specific ELISA kits following manufacturer's instructions (Akang et al, 2019). The commercial kits for examining these parameters were purchased from Nanjing Jiancheng Bioengineering Institute (Nanjing, China).…”
Section: Enzyme-linked Immunoabsorbent Assaymentioning
confidence: 99%
“…Moreover, like other natural compounds, naringenin has gained attention in the last year as a phytochemical with neuroprotective effects. Several studies described its effects and its ability to inhibit neuro-apoptosis, ameliorate cognitive impairment in different rodent models of neurodegenerative disorders, reduce oxidative stress improving mitochondrial dysfunction in neurons, support dopaminergic neurons and protect from neuroinflammation (Khan et al, 2012; Hsu et al, 2014; Manchope et al, 2017; Wang et al, 2017, 2019; Akang et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…In the study of Li et al 35 , which is an example of these studies, DMSO showed a protective effect in gut barrier by increasing the SOD activity and decreasing the MDA level in gut barrier dysfunction generated by zymosan. At the same time, there are other studies in the literature in which the antioxidant effects of DMSO could not be determined 38,39 . Different studies are needed to understand the effects of DMSO on oxidative system.…”
Section: ■ Discussionmentioning
confidence: 99%